Novel 5-functionalized-pyrazoles: Synthesis, characterization and pharmacological screening. Issue 17 (1st September 2015) - Doddaramappa, Shridevi D.; Lokanatha Rai, K.M.; Srikantamurthy, Ningaiah; Chandra; Chethan, Javarasetty
Graphical abstract